Structure-based designing and synthesis of 2-phenylchromone derivatives as potent tyrosinase inhibitors: In vitro and in silico studies. (1st April 2021) - Ashraf, Jamshaid; Mughal, Ehsan Ullah; Alsantali, Reem I.; Obaid, Rami J.; Sadiq, Amina; Naeem, Nafeesa; Ali, Anser; Massadaq, Anam; Javed, Qamar; Javid, Asif; Sumrra, Sajjad Hussain; Zafar, Muhammad Naveed; et al.
Graphical abstract: Highlights: Design and synthesis of 2-phenylchromones as the potent tyrosinase inhibitors. Compound 10 showed the excellent inhibitory activity (IC50 = 0.093 ± 0.003 µg/ml). Molecular docking studies of these compounds were performed. Structure-activity relationship (SAR) was established. ADME screening ( in silico ) of the synthesized analogues displayed drug-like nature. Abstract: The present study describes the discovery of novel inhibitors of mushroom tyrosinase enzyme. For that purpose, a series of varyingly substituted 2-phenylchromone analogues 1–28 were synthesized and characterized in detail by various spectroscopic techniques (UV–Vis, FTIR, 1 H NMR, 13 C NMR) and mass spectrometry. All the derivatives (1–28) were screened in vitro for their inhibitory potential against mushroom tyrosinase enzyme. Interestingly, all the synthetic compounds displayed good to excellent inhibitory activity with IC50 values ranging from 0.093 ± 0.003 μg/ml to 23.58 ± 0.94 μg/ml for brominated 3-hydroxy-2-phenylchromones and 0.22 ± 0.017 μg/ml to 22.22 ± 1.1 μg/ml for brominated 2-phenylchromones against tyrosinase in comparison to the standard kojic acid (IC50 = 1.79 ± 0.64 μg/ml). Remarkably, the bromine atoms attached on ring A attribute to increases the inhibitory potential of 2-phenylchromone moiety and anti-tyrosinase assay demonstrated that compound 10 ( IC50 = 0.093 ± 0.003 µg/ml) was found almost nineteenfold, 11 ( IC50 = 0.126 ± 0.015 µg/ml) fourteenfold and 26 ( IC50 = 0.22 ± 0.017 µg/ml) about eightfold more active than the positive control. Notably, among the already literature reported tyrosinase inhibitors, these analogues have been found the most active inhibitors of mushroom tyrosinase with the lowest possible IC50 values. To design and develop novel tyrosinase inhibitors using 2-phenylchromone as a structural motif in the future, a limited structure-activity relationship was established. Moreover, in silico studies were carried out to rationalize the binding mode of interactions of all the targeted compounds (1–28 ) with the active site of enzymes. The experimental and theoretical results are in parallel with one another. In addition, molecular description was performed with the drug-likeness and bioactivity scores. Computational analysis predicted that few compounds are in a linear correlation with Lipinski's RO5 indicating superb drug-likeness and bioactivity score for drug targets.